Prawo cywilne w działaniach administracji publicznej (administracji miar) – na gruncie systemu oceny zgodności z zasadniczymi wymaganiami. Tradycja i nowoczesność w instytucjach prawnych. - Żywicka, Agnieszka; Paździor, Mariusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article discusses the issues of applying the institutions of civil law in the activities of the economic administration based on the example of the administration of measures on the grounds of implemented tasks regarding the assessment system of conformity of goods with the essential requirements. The aim of the article is to identify new areas of applications of the civil law in the administration of measures and new legal phenomena taking place in the relations of administration authorities with entrepreneurs which are implied by the technical development in the area of metrology. Furthermore, the evaluation of their effects on the economy is presented both from the perspective of the protection of state interest and the interest of an individual entrepreneur. The following phenomena taking place under the influence of the appliance of civil-legal regulation method in metrology are presented: privatisation of public tasks from the field of metrology, appliance of civil-legal agreements in the activity of the administration of measures and the change in the status of administrative entities (offices of measures) as well as the situation of notified entities of the administration of measures in the conditions of parallel performed tasks in the conformity assessment system regarding the measuring instruments.